Historic tobacco legislation in Israel: a moment to celebrate - L. Rosen; S. Kislev; Y. Bar-Zeev; H. Levine (BMC, 2020)
Abstract Background Israel was once a leader in tobacco control, but fell behind other countries, particularly during the past decade, as smoking rates stagnated. Text Landmark tobacco control legislation, which banned advertising (with the exception of the print press) and limited marketing, was passed in Israel on Dec. 31rst, 2018. The changes occurred following years of attempts which culminated in successful last-minute efforts to promote the legislation just before the early disbanding of the 20th Knesset (Israeli Parliament). Regulations concerning marketing and advertising were substantially strengthened to address all tobacco, nicotine and smoking products. Digital media was included for the first time. Electronic cigarettes, which were previously largely unregulated, now fall under existing tobacco legislation. The changes overcame intense opposition from the tobacco lobby, and occurred despite the fact that the basic elements for prevention policy postulated by the Richmond model were not in place. Conclusions This legislation represents an important and long-awaited change in Israeli tobacco control policy. Many deficiencies in existing tobacco control regulation were overcome, and some measures went beyond current international regulations. The cohesive partnership between legislators, public health organizations and professionals, advocacy groups, academia, and leading journalists was critical to this success. The progress was lauded by the World Health Organization with its highest award for tobacco control, which was presented to Smoke Free Israel. This case study provides important lessons for up-to-date tobacco control policy, in the age of rapid global changes in the tobacco, vaping and nicotine landscape.